A phase-imaging technique for cyclotron-frequency measurements - Eliseev, Sergey; Blaum, Klaus; Block, M.; Dörr, Andreas; Droese, C.; Eronen, T.; Goncharov, Mikhail Leonidovich; Höcker, Martin Jürgen; Ketter, J.; Ramirez, E. Minaya; Nesterenko, D. A.; Novikov, Yu. N.; et al. (Applied physics. B, Lasers and optics, 2014)
A novel approach to mass measurements at the 10−9 level for short-lived nuclides with half-lives well below one second is presented. It is based on the projection of the radial ion motion in a Penning trap onto a position-sensitive detector. Compared with the presently employed time-of-flight ion-cyclotron-resonance technique, the novel approach is 25-times faster and provides a 40-fold gain in resolving power. Moreover, it offers a substantially higher sensitivity since just two ions are sufficient to determine the ion’s cyclotron frequency. Systematic effects specific to the technique that can change the measured cyclotron frequency are considered in detail. It is shown that the main factors that limit the maximal accuracy and resolving power of the technique are collisions of the stored ions with residual gas in the trap, the temporal instability of the trapping voltage, the anharmonicities of the trapping potential and the uncertainty introduced by the conversion of the cyclotron to magnetron motion.